Semiotics of Animal Narratives in Ancient Arabic Prose: The Monkey as a Model - فاطمة حسن السراحنه; فاطمة إبراهيم محيسن (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
This study revolves around the representations of the monkey in ancient Arabic literature from a semiotic perspective, to reveal the symbolic connotations associated with it in narrative texts. Writers have contributed to producing discourses and riddles extracted from its manifestations. The study relied on analyzing those selected texts that occupied a significant space in tales, maqamat, and others, with a focus on the cultural contexts that contributed to shaping the presence of the monkey as a multidimensional symbol. The study aims to answer major questions, most notably: How is the monkey used as a symbol that reflects societal and human issues? What are the cultural values ​​that appear by resorting to these representations? The presence of the monkey establishes a pattern of implications that reveal the wealth of human knowledge. The Arab’s observations have contributed to bridging the knowledge gap, recording human memory, and proving its experiences in roaming the animal world. The semiotic approach has been used as an analytical tool to decipher signals, codes, and signs in the texts under study, which has allowed the exploration of human statements with psychological and emotional connotations that were reflected in those texts, as the monkey is associated with the symbolism of betrayal, treachery, intelligence, insight, the ability to imitate and simulate, and class struggle, in addition to being a sign of gain and livelihood. In short: The monkey in its literary manifestation has transcended the usual vision as a sarcastic symbol to become an aesthetic tool for reading intertwined and complex human interactions and revealing diverse human values.